If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -5y = 4x + -9y + 13 Reorder the terms: 25 + -5y = 13 + 4x + -9y Solving 25 + -5y = 13 + 4x + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. 25 + -5y + 9y = 13 + 4x + -9y + 9y Combine like terms: -5y + 9y = 4y 25 + 4y = 13 + 4x + -9y + 9y Combine like terms: -9y + 9y = 0 25 + 4y = 13 + 4x + 0 25 + 4y = 13 + 4x Add '-25' to each side of the equation. 25 + -25 + 4y = 13 + -25 + 4x Combine like terms: 25 + -25 = 0 0 + 4y = 13 + -25 + 4x 4y = 13 + -25 + 4x Combine like terms: 13 + -25 = -12 4y = -12 + 4x Divide each side by '4'. y = -3 + x Simplifying y = -3 + x
| 15x-90=180 | | (5x+13)=(9x-31) | | 5t/3-t/2=1 | | 5-x=2.8 | | 16=6s-20 | | 2(5-y)=2x+30 | | 3x+2-4y=1x-4 | | 4x-3(x+1)=2(x-1)-16 | | 4y-x=12 | | 3y+20=5 | | 2(y-3x)=16-12x | | 11=44x-11y | | 8u+21=45 | | (X-4)=3x+2 | | 3-5x+9=25 | | f(x)=5x^2+bx+c | | f(x)=-7x^2+28x+25 | | 6x=27y-3 | | (6*6)*(4*4*4)= | | 5(X-13)-7(6-X)+29=50-3(8-X) | | a+(a-8)=44 | | %.317=164 | | x^2+6.91830971e-7x-4e-8=0 | | x^2-3x/7x | | p+(-4)=1 | | 1a(105/(35/7)) | | 8x+8=9x-7 | | 3x+2x-5=x+7 | | 1/4×16 | | x^2+x-0.058=0 | | 48/165 | | 1/3(9x-12)=1/4(16x-12) |